Relative forecasting performance of stock return for real activity in emerging markets of ASEAN countries - Lim, Yin Ping (2012)
This study has given a focus on the forecasting ability of stock market return for real GDP using stock market indicators. The forecasting ability of various financial variables particularly stock market variables for real economic activity is highly important since it signals whether policy makers should respond to changes in stock market returns. The present study is limited to the ASEAN-5 countries, as they are closely integrated and in addition it is the region that deserves more attention. In the analysis, a comparison is made between stock returns and other potential predictive variables in their ability to predict future variation in GDP. These potential predictive variables include interest rate,exchange rate, money supply and US GDP. From many forecasting methods, the out-of-sample rolling regression has been adopted to examine the forecasts over 1-, 2-, 4-, and 8-quaters ahead. Eveiws 7.0TM was employed for running the simulation and obtaining the results. The results showed that the stock returns serve as the best predictor, as it improves the forecast accuracy by up to 44%, meaning that there is a 44% reduction in the forecasting error, for the case of 2-quarter ahead GDP growth forecast in Malaysia. In addition, stock returns played as important role in GDP forecast for Singapore as it reduce the forecast error at most by 38%, Thailand by 18% and Indonesia by 7% in the 1-quarter ahead forecast, while the Philippines getting 8% forecast error reduction in the 4 quarter-ahead forecast.